Analysis of the Influence of Motivation, Human Resource Development, and Job Satisfaction on Employee Work Discipline at PT Panca Niaga Jaya Lestari Kisaran - Putri Melinda Cahya; Kholilul Kholik (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
This research aimed to investigate the influence of work motivation, human resource development, and job satisfaction on employee work discipline at PT Panca Niaga Jaya Lestari Kisaran. The population of this research comprised all non-managerial employees, totaling 89 individuals. The sample size was also 89 respondents, employing the saturated sampling technique. The research was conducted in the year 2024. This research used primary quantitative data collected through the distribution of questionnaires and processed using SPSS 24.0 with a multiple linear regression analysis model. The results indicated that work motivation, HR development, and job satisfaction, both partially and simultaneously, had a positive and significant effect on work discipline at PT Panca Niaga Jaya Lestari Kisaran. Work motivation emerged as the most dominant variable influencing work discipline, with a regression value of 0.459 and a t-value of 5.593. Approximately 90.4% of employee work discipline could be explained and derived from work motivation, HR development, and job satisfaction, while the remaining percentage was influenced by other factors. Work discipline had a very strong/close relationship with work motivation, HR development, and job satisfaction.